The Influence of Academic Supervision and Managerial Supervision by School Principals on the Performance of High School Teachers in West Aceh Regency - Burhanuddin; Nasir Usman; Niswanto (International Journal of Educational and Life Sciences, 2025)
The supervision conducted by school principals is an effort to assess teacher performance. Academic supervision involves planning, implementation, and evaluation of teaching. Managerial supervision ensures that administrative tasks run smoothly. This study aims to determine the influence of academic and managerial supervision by school principals on the performance of high school teachers in West Aceh Regency. A quantitative approach with multiple regression analysis was used. The sample consists of 123 public high school teachers in West Aceh. Data collection was done through questionnaires. The results show that: 1) Academic supervision has a positive effect on teacher performance, with a t-value of 9.442 > 1.979 and a regression coefficient of 0.651. 2) Managerial supervision also positively affects teacher performance, with a t-value of 9.011 > 1.979 and a regression coefficient of 0.634. 3) Both academic and managerial supervision have a combined positive effect on teacher performance, with an F-value of 47.635 > 3.07 and a determination coefficient (R²) of 44.3%. This means that 44.3% of teacher performance is influenced by academic and managerial supervision.